Ptolemy I and the transformation of Egypt, 404-282 BCE - McKechnie, Paul, 1957-; Cromwell, Jennifer. (Mnemosyne, Supplements, 2018)
Amyrtaeus, only pharaoh of the Twenty-eighth Dynasty, shook off the shackles of Persian rule in 404 BCE; a little over seventy years later, Ptolemy son of Lagus started the 'Greek millennium' (J.G. Manning's phrase) in Egypt-living long enough to leave a powerful kingdom to his youngest son, Ptolemy II, in 282. In this book, expert studies document the transformation of Egypt through the dynamic fourth century, and the inauguration of the Ptolemaic state. Ptolemy built up his position as ruler subtly and steadily. Continuity and change marked the Egyptian-Greek encounter. The calendar, the economy and coinage, the temples, all took on new directions. In the great new city of Alexandria, the settlers' burial customs had their own story to tell.